An investigation of coherent-correlator receivers for optical CDMA networks - Tanee Demeechai; O'Farrell, Timothy; Sharma, A.B.; Ahmed, Kazi Mohiuddin; Erke, Tapio J.; Asian Institute of Technology Partial (Bangkok : Asian Institute of Technology, 1994)
The multiple access performances of two techniques of coherent PO-CDMA, the code sequence-addressing network and the time-addressing network, are investigated taking into account the multiplicative MAI due to square law detection and the possibility that the laser frequency of each simultaneous user is not far from each other. The numerical results show that the performance of the time-addressing network is quite superior to that of the code-sequence addressing network. Moreover, the time-addressing network provides significantly high multiple access capability and throughput. Recommendations for further research are also presented.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Local area networks (Computer networks); Data transmission systems